Magnetostructural correlations in S = 1 trans-[Ni{(OPPh2)(EPPh2)N}2(dmso)2], E = S, Se, and related complexes. (1st September 2018) - Ferentinos, Eleftherios; Raptopoulou, Catherine P.; Psycharis, Vassilis; Terzis, Aris; Krzystek, J.; Kyritsis, Panayotis
Graphical abstract: The structural and magnetic properties of the pseudo-octahedral trans -[Ni{(OPPh2 )(EPPh2 )N}2 (dmso)2 ], E = S, Se, complexes, are investigated by X-ray crystallography and HFEPR spectroscopy. Initial magnetostructural correlations are drawn among the sub-family of trans -[Ni{(OPPh2 )(EPPh2 )N}2 (sol)2 ], sol = dmso, dmf, thf, complexes. Abstract: In this work, the structural and spectroscopic characterization of trans- [Ni{(OPPh2 )(EPPh2 )N)}2 (dmso)2 ], E = S, Se, complexes is described. These Ni(II) complexes contain two chelating (O, E) = [(OPPh2 )(EPPh2 )N)] − ligands, as well as two dimethyl sulfoxide (dmso) molecules coordinated via their O atoms. X-ray crystallography studies revealed a highly anisotropic pseudo-octahedral trans -NiO4 E2 coordination environment, extending the literature dataset of their trans- [Ni(O, E)2 (sol)2 ], sol = dmf, thf, counterparts. Collectively considered, these six complexes contain similar coordination spheres, exhibiting, however, subtle structural differences due to the nature of the donor atom (E) and solvent molecule (sol) coordinated to Ni(II). The spin Hamiltonian parameters of S  = 1 trans -[Ni(O, Se)2 (dmso)2 ], E = S, Se, were accurately determined by high-frequency and -field EPR spectroscopy, applying a methodology already used for trans- [Ni(O, E)2 (sol)2 ], sol = dmf, thf. Magnetostructural correlations are explored between all members of this sub-family of Ni(II) complexes.